2006
DOI: 10.1161/circulationaha.105.548016
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Listing for Cardiac Transplantation for Failed Fontan

Abstract: Background-The Fontan procedure is a successful palliation for children with single-ventricle physiology; however, many will eventually require heart transplantation. The purpose of this study was to determine risk factors for death awaiting transplantation and to examine results after transplantation in Fontan patients. Methods and Results-A retrospective, multi-institutional review was performed of 97 Fontan patients Ͻ18 years of age listed at 17 Pediatric Heart Transplant Study centers from 1993 to 2001. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
174
2
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(186 citation statements)
references
References 18 publications
5
174
2
5
Order By: Relevance
“…These patients, typically adolescents or adults, present late with insidious decline, often "tolerating" their symptomatology. PLE without transplantation carries a 50% mortality at 5 years; resolution of PLE post-OHT is reported in 100% of early survivors, highlighting its development as a compelling indication for transplant (26,27). However, destabilization of multiple homeostatic mechanisms leads to high peri-operative risk which must be considered when counselling patients (4,28).…”
Section: Ple and Pbmentioning
confidence: 99%
See 2 more Smart Citations
“…These patients, typically adolescents or adults, present late with insidious decline, often "tolerating" their symptomatology. PLE without transplantation carries a 50% mortality at 5 years; resolution of PLE post-OHT is reported in 100% of early survivors, highlighting its development as a compelling indication for transplant (26,27). However, destabilization of multiple homeostatic mechanisms leads to high peri-operative risk which must be considered when counselling patients (4,28).…”
Section: Ple and Pbmentioning
confidence: 99%
“…However, recent interrogation of the Paediatric Heart Transplant Study Database showed improved 1-year survival from 71% [1993][1994][1995][1996][1997][1998][1999][2000][2001][2002][2003][2004][2005][2006] to 89% [2007][2008][2009][2010][2011][2012][2013][2014] for those undergoing OHT for FFP, reaching comparable outcomes to other CHD patients (42). Other paediatric registry data has shown comparable outcomes between Fontan and nonFontan SV OHT patients (27,43,44). In our own adult data of OHT for FFP, we have shown a 2-fold improvement in 30-day survival from 40% to 76% over similar eras (24).…”
Section: Mortality In Sv Heart Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the Fontan patient, protein losing enteropathy is another important manifestation of the failing heart. 6 …”
Section: Symptomsmentioning
confidence: 99%
“…Because PLE has adverse prognostic consequences, reversibility of PLE in HF patients is critically important when considering radical HF therapy, such as cardiac transplantation. PLE has been shown to reverse after transplant in young patients with failed Fontan circulation,8 but its reversibility is not established in other conditions and in adults. Here, we report a patient in whom PLE with immune deficiency developed as a complication of hypokinetic non‐dilated cardiomyopathy, probably due to combination of increased ventricular stiffness and encircling epicardial electrode,9 that completely resolved after heart transplantation.…”
Section: Introductionmentioning
confidence: 99%